2015
DOI: 10.1061/(asce)cc.1943-5614.0000524
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Carbon-Fiber-Reinforced Polymer Stirrups in Prestressed-Decked Bulb T-Beams

Abstract: Eleven decked bulb T beams were constructed, instrumented, and tested under shear loading to failure. Nine beams were reinforced and prestressed with carbon-fiber composite cable (CFCC) strands, whereas one beam was prestressed with conventional lowrelaxation steel strands and one beam was reinforced with non-prestressed CFCC strands. Half the span of each beam was reinforced with CFCC stirrups, whereas the other half was reinforced with conventional steel stirrups. Both ends of each beam were tested to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Acoustic emission (AE) [4][5][6] is also an excellent method to monitor the materials' prestressing, and it uses the characteristics of acoustic information to detect the location and size of an acoustic source. Other studies [12][13][14][15] such as the application of a new material (unbonded carbon fiber) and technologies (novel optico-acoustic and sensors on a single optical fiber) in the prestressed concrete have also made some progress.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emission (AE) [4][5][6] is also an excellent method to monitor the materials' prestressing, and it uses the characteristics of acoustic information to detect the location and size of an acoustic source. Other studies [12][13][14][15] such as the application of a new material (unbonded carbon fiber) and technologies (novel optico-acoustic and sensors on a single optical fiber) in the prestressed concrete have also made some progress.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that FRP reinforced decked bulb T-beams could be safely applied to improve the performance and prolong the life span of bridges. Shear behaviour of prestressed decked bulb T-beams having CFCC stirrups was investigated by Grace et al [13]. The effect of shear span-to-depth ratio and transverse reinforcement type on the shear carrying capacity was studied in this research.…”
Section: State Of the Fieldmentioning
confidence: 96%
“…The use of FRP as structural reinforcement, in turn, provides the potential advantage of lowered maintenance costs and extended service life for several types of structures, including bridge deck slabs, bridge piers and piles, abutments, tunnels, walls and other structures exposed to corrosive environments. 35 Over the last decade, FRP tendons have been introduced into the civil-engineering industry to overcome the corrosion problem of steel tendons in prestressing applications including bridges and parking garages. 5,6 The commercially available FRP tendons are produced from a wide variety of fibers and resins and in a broad range of shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…35 Over the last decade, FRP tendons have been introduced into the civil-engineering industry to overcome the corrosion problem of steel tendons in prestressing applications including bridges and parking garages. 5,6 The commercially available FRP tendons are produced from a wide variety of fibers and resins and in a broad range of shapes and sizes. 7 However, the ACI 8 recommended aramid and carbon fibers for prestressing tendons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation